2021
DOI: 10.1177/09721509211036860
|View full text |Cite
|
Sign up to set email alerts
|

Trade Credit as a Determinant of Firm’s Financial Performance: Moderating Role of Bank Financing

Abstract: The objective of study is to find out the impact of trade credit on a firm’s financial performance and how this effect diversifies when enterprises acquire bank loans to finance the trade credit channel. To achieve the objective, we employ the data of 6,654 non-financial-sector firms from 12 Asian economies and apply fixed-effects model to estimate the regression. The statistical output of the model provides consistent evidence that the firms that adjust their trade credit activities through bank financing per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
0
7
0
3
Order By: Relevance
“…All these measures have been used in prior studies (Bui, 2020; Pan et al. , 2020; Farooq et al. , 2021).…”
Section: Sample and Research Methodologymentioning
confidence: 99%
“…All these measures have been used in prior studies (Bui, 2020; Pan et al. , 2020; Farooq et al. , 2021).…”
Section: Sample and Research Methodologymentioning
confidence: 99%
“…Moreover, Farooq et al . (2021) found that Asian firms that improve their trade credit activities perform better financially.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Saeed and Zureigat (2020) document that CSR positively affects the buyer and supplier sides of trade credit. Moreover, Farooq et al (2021) found that Asian firms that improve their trade credit activities perform better financially.…”
Section: Corporate Social Responsibility and Financial Distressmentioning
confidence: 99%
“…These are: Character, capacity, collateral, capital and condition. Character basically is a tool that provides weighting values for various characteristics of a client appraisal and the total weighted score of the applicant is used to estimate his credit worthiness (Farooq & Ahmed, 2021). This is the personal impression the client makes on the potential lender.…”
Section: Credit Standardsmentioning
confidence: 99%